Bread Sales Information System at Satria Bread Shop: Sistem Informasi Penjualan Roti di Toko Satria Roti - Cahyani, Ravica Eka; Fitrani, Arif Senja (Procedia of Engineering and Life Science, 2023)
In the current era of globalization, technological developments are progressing very rapidly so that with the advancement of this technology it can facilitate humans in various activities. In this research, a Web-Based Bread Sales Information System will be built at the Satria Roti Shop, Sidoarjo, which currently still uses the manual way of transacting with customers, so that customer service is still not optimal and efficient.The method used in this study is the waterfall method and software as follows: Visual code as an editor, React programming language, Javascript framework, Apache web server and MySQL as the database.This research will produce a Web-Based Bread Sales Information System at the Satria Roti Shop, Sidoarjo, which has an appropriate interface and can facilitate the process of selling bread transactions efficiently and practically.